(untitled) (Bangladesh Journal of Urology, 2026)
Objectives: To evaluate whether combination therapy with Dutasteride and Tamsulosin is more effective than Dutasteride monotherapy for improving symptom of BPH. Patient and method: This hospital based, prospective, randomized, comparative study will be conducted in Urology Dept. BSMMU from January 2011 to June 2012.Total 160 cases were selected according to inclusion and exclusion criteria. 80 case for combination therapy and 80 cases for monotherapy. Men 50-75 years with clinical diagnosis of prostatic hyperplasia, international prostate symptom score points 8 to 35, prostate volume 30 to 50 cc, total serum prostate specific antigen 1.5 to <4 ng/ml and peak urinary flow rate 5 to 15 ml/sec were randomized to 0.5 mg Dutasteride or the combination of 0.5 mg Dutasteride and 0.4 mg Tamsulosin on a daily for 12 months. Symptoms were assessed at 6 month and 12 months. Result: Combination therapy resulted in significant improvements in symptoms. There was significantly greater improvement from baseline in Qmax, IPSS and Prostate Volume for combination therapy vs Dutasteride from month six. Drug related adverse events with combination therapy is not significant. Conclusion: In men with moderate to severe lower urinary tract symptoms and prostate enlargement (30 cc or greater) combination therapy provides a significantly greater degree of benefit than Dutasteride monotherapy. Bangladesh J. Urol. 2025; 28(2): 112-118